EFEKTIVITAS PENGGUNAAN MOLYMOD BERBANTUAN APLIKASI CHEMDRAW PADA MODUL PRAKTIKUM KIMIA ORGANIK II TOPIK STEREOKIMIA - Dewi Handayani; Sura Menda Ginting; Nurhamidah; Nadia Amida (University of Bengkulu, 2026)
This study aims to improve the quality of learning in Organic Chemistry II. Based on the problems raised, the specific objective of this study is to determine the effectiveness of using molymod media assisted by the ChemDraw application in improving students' understanding of stereochemistry material in the practicum module. To determine student learning outcomes after using molymod media assisted by the ChemDraw application on stereochemistry material in the practicum module. The type of research used is an experimental method with the aim of determining the effect of a treatment on something under controlled conditions. This study uses a pre-experimental design of the one-group pretest-posttest type. Data collection techniques include interviews, observations, tests, and student response questionnaires. Based on the average N-Gain calculation, it is known that the increase in student learning outcomes obtained an average score of 0.86, which is classified as high criteria (0.70 ≤ n ≤ 1.00), so it can be said that there was a very good increase in student learning outcomes after using molymod assisted by the ChemDraw application on the organic chemistry II practicum module on the topic of stereochemistry. The practical process of stereochemistry topics using Molymod, assisted by the ChemDraw application, can encourage students to understand the concept of the material through exploration activities, visualization, and direct manipulation of molecular models. The students' response to the practical module presented in the form of an integration of the use of Molymod and ChemDraw was an average score of 91%, which is classified as very good. Keywords: molymod; ChemDraw; learning outcomes; stereochemistry